Medical tourism: its research and implications for public health - Klímová, Blanka; Kuča, Kamil (Central European Journal of Public Health, 2020)
OBJECTIVE: The purpose of this article is to describe current research trends in medical tourism and implications for public health, especially in destination countries. METHODS: The methods used for this article include a literature review of available sources on the research topic in the world's acknowledged databases Web of Science, Scopus, MEDLINE, and ScienceDirect. RESULTS: The findings indicate that there is no consensus on the definition of medical tourism. However, there are a few conceptual models which can be used in further medical tourism research and practice. The findings also reveal that there are still certain issues, which hinder the fast growth of medical tourism, such as unclear impact on healthcare systems, ethical concerns or a lack of effective tools for the measurement of quality assurance of the medical tourism services and their products. CONCLUSIONS: There is a need for data collection on medical tourism, both at national and worldwide level to provide a realistic picture of this evolving field of tourism as well as implications for public health in destination countries.
Keywords: Research; výzkum; Public Health; veřejné zdravotnictví; lidé; zdravotní turistika; Medical Tourism; Humans